From Indonesia to China: The Evolving Landscape of Santri Diplomacy - Xue Song; Virdika Rizky Utama (Islam Nusantara: Journal for the Study of Islamic History and Culture, 2025)
This paper critically explores the evolution, challenges, and unique characteristics of santri diplomacy in the context of China. While globally, Indonesian Islamic organizations such as Nahdlatul Ulama (NU) and Muhammadiyah have institutionalized santri-driven diplomacy, the Chinese context reveals a different pattern. Due to China’s strict regulations on religious expression and activities, santri diplomacy in this setting operates primarily through cultural channels rather than overt religious advocacy. In China, individual santri—particularly students, scholars, and members of the Indonesian diaspora—serve as informal cultural ambassadors. Utilizing digital platforms and social media, these actors promote a positive image of Indonesia, initiate people-to-people exchanges, and foster intercultural understanding. Their activities include organizing cultural events, academic collaborations, and sharing narratives about Indonesia’s pluralistic Islam. These efforts reflect a shift from institutional diplomacy to personalized, grassroots cultural diplomacy. A distinctive feature of santri diplomacy in China is its “reverse advocacy” function: many santri seek to counter the often negative or simplistic portrayals of China’s religious environment in Indonesian media. By offering nuanced explanations and first-hand perspectives, they aim to reduce public misunderstanding and foster more balanced views among Indonesian Muslims. As diplomatic, economic, and educational relations between Indonesia and China deepen, the strategic importance of santri diplomacy will likely increase. To maximize its impact, it is essential to support santri actors through institutional recognition, capacity-building programs, and collaborative frameworks involving Islamic organizations, the Indonesian government, and educational institutions. Empowering these cultural agents will ensure that santri diplomacy continues to serve as a bridge of understanding in a complex geopolitical landscape.